Physicochemical and radiological characterization of flue gas desulfuration waste samples from Brazilian coal-fired power plants - Denise Fungaro; Lucas Grosche; Paulo Silva (Brazilian Journal of Radiation Sciences, 2023)
Flue gas desulfurization (FGD) waste is an industrial by-product generated during the flue gas desulfurization process in coal-fired power plants. This by-product contain trace quantities of naturally occurring radionuclides and elements such as As, Ba, Co, Cr, Zn. The characteristics of FGD waste are important for its reuse and are mainly depend on the desulfurization process. In this work, two types of FGD materials collected from three coal-fired power plants using semi-dry and wet processes were characterized by X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), X-ray fluorescence (XFR) and particle size analysis. The radioactive content of 238U, 232Th, 228Th, 226Ra, 228Ra, 210Pb and 40K and trace elements were also determined using Neutron activation analysis and Gamma-ray spectrometry. The major constituents for all samples were Ca, Si, S, Al and Fe. Wet FGD by-product presented also high magnesium content. The wastes contain mainly semi-hydrate calcium sulfite and calcium sulfate. The particle size of FGD from semi-dry process was lower than that from the wet process. The average activity concentration of 238U, 232Th, 226Ra, 210Pb, 228Ra, 228Th and 40K varied between were 50-71, 33-42, 28-52, 113-150, 26-33, 33-39, 161-390 Bq kg-1, respectively. According to the results of leaching and solubilization tests, FGD samples were classified as non-hazardous and non-inert. The obtained data are useful for evaluation of possible applications of FGD by-products.